Metabolic Reprogramming at the Edge of Redox: Connections Between Metabolic Reprogramming and Cancer Redox State - Serrano, José J.; Medina, Miguel Ángel (International journal of molecular sciences, 2025)
The importance of redox systems as fundamental elements in biology is now widely recognized across diverse fields, from ecology to cellular biology. Their connection to metabolism is particularly significant, as it plays a critical role in energy regulation and distribution within organisms. Over recent decades, metabolism has emerged as a relevant focus in studies of biological regulation, especially following its recognition as a hallmark of cancer. This shift has broadened cancer research beyond strictly genetic perspectives. The interaction between metabolism and redox systems in carcinogenesis involves the regulation of essential metabolic pathways, such as glycolysis and the Krebs cycle, as well as the involvement of redox-active components like specific amino acids and cofactors. The feedback mechanisms linking redox systems and metabolism in cancer highlight the development of redox patterns that enhance the flexibility and adaptability of tumor processes, influencing larger-scale biological phenomena such as circadian rhythms and epigenetics.